Clinical profile, risk factors and outcome of ischemic heart disease patients at tertiary care centre - Vasava, Jignesh F.; Patel, Vaishali G. (International Journal of Advances in Medicine, 2018)
Background: Coronary heart disease is responsible for more deaths and disability in developed world, now affecting developing countries. The present study aims to evaluate clinical course, identification of risk factors and outcome of unstable angina. Methods: An observational study of 30 days follow up of 100 patients of newly diagnosed UA was conducted. Sociodemographic, clinical, family h/o risk factors, dietary, other lifestyle characteristics, Standard 12 lead ECG and BP recorded. Blood was collected for routine investigations and cardiac enzymes (serum Trop-T Quantitative and CPK-MB levels). Blood was Collected in fasting state (glucose and lipid profile) and after4 hrs of routine lunch for Triglyceride measurement. Patients were observed for complications after hospital discharge on OPD basis. Results: Middle aged patients are more likely to be selected for study (mean age 51.2±6.4) being M:F ratio of 1.5:1. Amongst males 82%were smokers. 68 patients were having Postprandial triglyceride >160 mg% while 58 had low HDL levels(<40mg%).Amongst 100 patients, 68% and 62% found to be Diabetic and hypertensive respectively. Hospital outcome was good.81.2% patients remained free of cardiac events during 30 days follow up while 13.7% admitted with recurrent angina. No mortality during entire study period. Conclusions: Ischemic heart disease entails high socioeconomic burden due to increased morbidity and mortality. smoking, hypertension, diabetes mellitus and dyslipidemia are important cardiovascular risk factors in present study. Postprandial hypertriglyceridemia was found to be strongly associated with Diabetes Mellitus. Postprandial hypertriglyceridemia despite normal fasting triglyceride may be independent risk factor for atherosclerosis subsequently ischemic heart disease. Early identification, treatment and prevention of cardiovascular risk factors can decline the incidence, complications and related mortality.